English-medium instruction in Singapore higher education: policy, realities and challenges. Issue 10 (26th November 2017) - Bolton, Kingsley; Botha, Werner; Bacon-Shone, John
ABSTRACT: Within the Asian region, Singapore has long been seen as a leader within the field of higher education, with an unmatched record of success in implementing English-medium instruction (EMI) at all levels of education, including colleges and universities. This present study reports on a large-scale survey carried out at one of Singapore's major universities on the use of English as a teaching medium at both undergraduate and postgraduate level. Key findings from the survey foreground the difficulties and needs of students coping with EMI instruction at undergraduate and postgraduate levels. One important result here highlights the specific problems of overseas postgraduate students (including many from mainland China), a finding that resonates with the sociolinguistics of higher education in many other international universities in an era of global education.